ANALISIS FAKTOR PELAYANAN DAN KEPERCAYAAN DALAM KEPUTUSAN PENERIMAAN KREDIT BNI FLEKSI PEGAWAI (STUDI PADA BNI CABANG AMBON) - Mahulette, Eva Ayu Syafitri; Syaifullah, Yunan (Program Studi Ekonomi Pembangunan, 2022)
This study aims to analyze the factors of service and trust in the decision to give BNI credit at PT. Bank Negara Indonesia (Persero) Tbk. Ambon Branch. Where this research was conducted using quantitative analysis methods, namely by using the instrument test (validity test and reliability test), multiple linear regression analysis test, and hypothesis testing (T test and F test). The results of the study indicate that there is a partially significant effect on the Service Variable (X1) and the Trust Variable (X2), a positive effect with significant results on the decision (Y) of BNI Flexi lending at PT. Bank Negara Indonesia Ambon Branch. With five elements used but with different definitions of each variable, but using all the same tests, in this case the results has an equally influential effect on the decision (Y). The tests carried out, such as the Validity Test, Reliability Test, Multiple Linear Regression Analysis, F Test and t Test.